Re-design Road Geometric Trends: A Systematic Literature Review - Rahayu, Azi Juliar; Kamaludin, Kamaludin; Firmansyah, Rendy Rizkyta; Rijaluddin, Arief; Prasetijo , Joewono (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research explores the prevailing patterns in the re-design of road geometry by employing a Systematic Literature Review (SLR) methodology. A total of 1,000 scholarly articles, spanning the years 2000 to 2025, were collected using Google Scholar using the Publish or Perish software. Through this process, the study uncovers major themes, advancements, and research gaps related to geometric road design. The search utilized keywords such as "Geometric Re-design," "Horizontal Alignment," and "Traffic Flow Efficiency." To analyze and visualize data, VOSviewer was used to illustrate the interconnections between keywords and observe publication trends. The results indicate a notable rise in research publications between 2011 and 2023, with recurring themes such as case studies, road alignment, and safety standing out as primary research interests. Prominent publishers like ProQuest and Elsevier have made substantial contributions, reflecting the international breadth and variety of the studies. This review highlights the essential function of geometric road re-design in enhancing traffic safety, streamlining vehicle movement, and informing future infrastructure development. These insights are particularly beneficial for academics, engineers, and decision-makers aiming to improve the efficiency and effectiveness of transportation networks.